Pengaruh Pengungkapan Corporate Social Responsibility (CSR) Terhadap Nilai Perusahaan Pada Perusahaan Industri Barang Konsumsi Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2016-2018 - Gea, Annisa Fitri; Ovami, Debbi Chyntia (lppm.eka-prasetya.ac.id, 2020)
The company's goal is to implement CSR to have a positive impact on the environment and society as a sense of social responsibility to the environment around the company. Implementation of Corporate Social Responsibility (CSR) will also increase the value of the company. The value of a company will increase if the company pays attention to the economic, social and environmental or environmental dimensions that exist around the company. This study aims to determine the effect of Corporate Social Responsibility (CSR) disclosure on company value in consumer goods industry companies listed on the Indonesia Stock Exchange (BEI) in 2016-2018. The method used in this research is quantitative method. The population in this study were consumer goods industry companies listed on the Indonesia Stock Exchange (BEI) in 2016-2018 totaling 53 companies. The sampling technique uses a purposive sampling method with a sample of 15 companies. Analysis of the data used is simple linear regression analysis. The results of this study indicate that the disclosure of Corporate Social Responsibility (CSR) has a positive and significant effect on firm value with a coefficient of 2169,806 and a significance of 0,000